Media Convergence Journalists Perspectives on Diversity News - Moehammad Gafar Yoedtadi; Lusia Savitri Setyo Utami (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2021)
The issue of diversity is a sensitive issue. if not handled wisely, it will become a problem that degrades national harmony. The mass media which have ideal functions as a medium of information, pay less attention to the issue of diversity. Though the role of mass media, especially convergent media is very influential on this matter. This research was conducted with the aim to get an overview of the views of journalists from the convergent media Liputan 6.com in seeing the issue of diversity. Journalists who become participants are from the senior level (deputy chief editor), middle (editor), and junior (reporter). The research method uses qualitative with a phenomenological approach. The theoretical basis used in this study is peaceful journalism and agenda setting. Data collection is done by in-depth interviews and observations. The results showed that the editorial policy of Liputan6.com was careful in reporting on the topic of diversity. The policy has been well understood by each level of journalist. In addition there is a personal awareness of each participant to prioritize caution in reporting the topic of diversity.